VD_FINDINFO Arrêt / 2011 / 509 vom 5. April 2011 - VD Tribunal cantonal (2011)
TUTELLE, ALCOOLISME, MALADIE MENTALE, PRIVATION DE LIBERTÉ À DES FINS D'ASSISTANCE | 369 al. 1 CC, 369 CC, 370 CC, 397a al. 1 CC, 397a CC, 379 CPC, 393 CPC, 398a CPC, 489 CPC